Application of “Six Rights” on Medication Administration by Nurse and Patient Satisfaction - Imelda Rahmayunia Kartika; Vivi Melani (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2017)
Introduction: Giving the medications, nurse should pay attention to the principles of “six of rights